The effect of caring on post-bereavement outcome: Research gaps and practice priorities - Breen, Lauren (Maney Publishing, 2012)
Family caregivers are the primary caregivers of family members over the course of illness. Some caregivers exhibit elevated levels of distress following the death of the person for whom they were caring. Despite the practical relevance for providing supports and services to caregivers and families, pre- and post-bereavement, the effect of caregiving on bereavement is obscured. In examining the research literature on caregiving and bereavement, three methodological limitations were identified – caregivers’ perspectives on preparing for the death of the person for whom they were caring is typically not assessed; the effect of caring on post-death adjustment tends to be assessed qualitatively, cross-sectionally, and retrospectively; and there is a lack of adequate comparison groups. This paper highlights the need to address two important gaps in understanding the effects of caregiving and bereavement: (1) caregivers’ understandings and experiences of the anticipating and preparing for the death of the person for whom they are caring, and (2) the relationship between caregivers’ pre-death grief and distress and post-death adjustment. Caregivers relieve significant costs from the health system, and improved support, pre- and post-bereavement, will continue to benefit them as well as society. Without significant research investment, palliative care services will continue to operate without a suitable evidence base to support their bereavement care efforts.